Potential use of the bioactive compounds of the olive mill wastewater: Monitoring the aldehydes, phenolic compounds, and polymerized triacylglycerols in sunflower and olive oil during frying. Issue 11 (25th August 2022) - Harzalli, Zina; Willenberg, Ina; Medfai, Wafa; Matthäus, Bertrand; Mhamdi, Ridha; Oueslati, Imen
Abstract: The current study aims to investigate the application of the olive mill wastewater (OMW) extract (100 ppm) as additive to the refined sunflower oil and olive oil to reduce the formation of the oxidation products during deep frying of chicken and potato. The production of polymerized triacylglycerols ( p TAG) and aldehydes was lower during frying in olive oil than in enriched refined oil. The highest percentage of polyunsaturated fatty acids in refined oil exhibits a great tendency to form polymeric compounds. The enrichment of sunflower oil with OMW extract reduces the formation of p TAG and aldehydes, whereas the enrichment of olive oil with OMW extract showed an increase in the formation of p TAG and promoted the biosynthesis of aldehydes whose rate remains significantly lower than that observed in enriched sunflower oil. The production of polymerized and aldehydic compounds was more pronounced when chicken was fried compared with potatoes. For the phenolic alcohols, their degradation was reached at the end of the experimentation. Novelty impact statement: Olive mill wastewater (OMW) is a source of bioactive molecules that can be extracted and valorized in several industrial sectors. OMW extract reduces the production of p ‐TAG and aldehydic products during frying foods in refined sunflower oils Frying of foods in olive oil without any additive is healthier than frying in enriched refined oils.